The Effects of Sesquiterpene Lactones on the Differentiation of Human or Animal Cells Cultured In-Vitro: A Critical Systematic Review - Fateh, Sepand Tehrani; Fateh, Sahand Tehrani; Shekari, Faezeh; Mahdavi, Majid; Aref, Amir Reza; Salehi-Najafabadi, Amir (Frontiers in Pharmacology, 2022)
Cellular differentiation is pivotal in health and disease. Interfering with the process of differentiation, such as inhibiting the differentiation of adipocytes and inducing the differentiation of cancer cells, is considered a therapeutic approach. Sesquiterpene lactones, primarily found in plants, have been attracted attention as differentiating/dedifferentiating agents tested on various human or animal cells. However, a consensus on sesquiterpene lactones’ effects and their mechanism of action is required. In this sense, through a systematic review, we have investigated the differentiating/dedifferentiating effects of sesquiterpene lactones on human or animal cells. Thirteen different cell lines originated from humans, mice, and rats, in addition to the effects of a total of 21 sesquiterpene lactones, were evaluated in the included studies. These components had either inducing, inhibiting, or no effect on the cells, mediating their effects through JAK-STAT, PI3K-Akt, MAPK, NFB, PPAR pathways. Although nearly all inducing and inhibiting effects were attributed to cancerous and normal cells, respectively, this is likely a result of a biased study design. Few studies reported negative results along with others, and no study was found reporting only negative results. As a result, not only are the effects and mechanism of action of sesquiterpene lactones not vivid but our knowledge and decisions are also misconducted. Moreover, there is a significant knowledge gap regarding the type of evaluated cells, other sesquiterpene lactones, and the involved signaling pathways. In conclusion, sesquiterpene lactones possess significant effects on differentiation status, leading to potentially efficient therapy of obesity, osteoporosis, and cancer. However, reporting negative results and further investigations on other cells, sesquiterpene lactones, and signaling pathways are highly suggested to pave the path of sesquiterpene lactones to the clinic more consciously.